COMPARATIVE STUDY: LEARNER’S EFL MASTERY THROUGH THE COLLABORATIVE LEARNING METHOD - Sitti Mukamilah; Ahmad Ahmad (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
Collaborative learning means instructional arrangement involves two or more learners working together on a share learning goals. Learners are encouraged to ask question, give elaborated explanations, exchange arguments, formulated new ideas and problem solution during teaching and learning activities. The aim of this study was to know the significant comparation on learner’s EFL mastery by implementing collaborative method at classroom teaching learning. The research has been analyzed forward experimental research design; The purposes were formulated; to examined the impact of Collaborative Learning on Learner’s EFL Mastery by conducting a quasi-experimental method; it qualitatively investigated learners’ perceptions of Collaborative Learning. The data exhibited that Collaborative learning had significant impact on leaner’s EFL mastery. Subsequently, the data result of independent sample t-test, there was significant difference in post-test result between experimental class and control class (p=0.000≤0.05), actually post-test of the experimental class means (M=10.81) and post-test of the control class means (M=8.45). Collaborative Learning led learners to accept differences and to make those differences comparative sources in order to be more knowledgeable as well as wiser while dealing with a problem at reading material of EFL learning during the class activities. .  The result of study depicts that collaborative learning is contributive to learners’ emotional awareness, learning motivation, cognitive development, and broad-mindedness.